Local buckling of steel plates in composite members with tie bars under axial compression. (15th February 2020) - Hu, Hong-Song; Fang, Peng-Peng; Liu, Yang; Guo, Zi-Xiong; Shahrooz, Bahram M.
Highlights: 12 specimens with only the steel plates resisting the axial load were tested. The buckling modes for different arrangements of tie bars were examined. The average stress-strain curves of the steel plates were investigated. Simplified equations for estimating the strengths of the steel plates were developed. Abstract: Tie bars have been frequently used in square or rectangular concrete-filled steel tubular (CFST) columns and concrete-filled steel plate (CFSP) composite shear walls for delaying local buckling of the steel plates and also improving the concrete confinement. This study investigated the entire response of steel plates in composite members with tie bars. Twelve specimens were designed and tested under axial compression. In these specimens, only the steel plates resisted the axial load, and the concrete was only used to restrain the inward buckling of the steel plates. The effects of the width-to-thickness ratio of the steel plate and the ratio of the vertical spacing of the tie bars to the steel plate width (abbreviated as vertical-spacing-to-width ratio) were investigated. It was found that the increase in the performance of the steel plates due to the tie-bar restraint was quite limited when the vertical-spacing-to-width ratio was 1/2 and became more significant when this ratio decreased to 1/3. The elastic buckling stresses of rectangular plates having boundary conditions similar to those in composite members were computed using the finite element method for further strength evaluation of the steel plates. It was found that the effect of the columns of tie-bars on the elastic buckling stress increased as the vertical-spacing-to-width ratio decreased and was negligible when this ratio was larger than 0.6. Simplified equations for estimating the maximum strength and reserved strength (defined as the average stress corresponding to the average strain of 3%) of the steel plates in composite members with tie bars were developed based on the test results and elastic buckling analyses.